Case Study of the Russia-Ukraine War from the Perspectives of Strategy and International Relations and Its Implications for the Indonesian Navy - Suhendra, Agung; Darmawan, Budi; Nugraha , Dany Wira (Journal of Industrial Engineering & Management Research, 2025)
The relationship between Russia and Ukraine prior to the 2022 conflict was marked by tension, driven by issues of territorial boundaries, political identity, and economic interdependence, with Russia seeking to maintain its influence over Ukraine. Tensions escalated after Ukraine halted negotiations with the European Union in 2013, triggering the Euromaidan protests and worsening bilateral relations. Although Ukraine strengthened ties with the EU and sought NATO membership, Russia’s threats to these aspirations culminated in Russia’s military invasion on February 24, 2022, after Volodymyr Zelenskyy defied these threats and pursued his plans. The aim of this study is to analyze the Russia-Ukraine war from the perspectives of strategy and international relations, as well as its implications for the Indonesian Navy. This research adopts a qualitative approach. The findings show that the Russia-Ukraine war reflects a long-standing geopolitical and geo-economic tension between the two nations, triggered by differences in political orientation, identity, and control over strategic territories. The conflict highlights the significance of political identity and international alliances in shaping the direction of war and how geopolitical dynamics can lead to open conflict. In facing this war, Russia relied on its large conventional military strength to quickly defeat Ukraine, while Ukraine, despite limited resources, leveraged international support to strengthen its resilience. The impact of the war is far-reaching, affecting not only the two countries but also global stability through disruptions in energy supplies, economic downturns, inflation, and food crises.